Risk Factors and Outcomes of Pulmonary Hypertension in Infants With Bronchopulmonary Dysplasia: A Meta-Analysis - Chen, Ying; Zhang, Di; Li, Ying; Yan, Aixia; Wang, Xiaoying; Hu, Xiaoming; Shi, Hangting; Du, Yue; Zhang, Wenhui (Frontiers in Pediatrics, 2021)
Background: Pulmonary hypertension is one of the most common co-morbidities in infants with bronchopulmonary dysplasia (BPD), but its risk factors are unclear. The onset of pulmonary hypertension in BPD has been associated with poor morbidity- and mortality-related outcomes in infants. Two review and meta-analysis studies have evaluated the risk factors and outcomes associated with pulmonary hypertension in infants with BPD. However, the limitations in those studies and the publication of recent cohort studies warrant our up-to-date study. We designed a systematic review and meta-analysis to evaluate the risk factors and outcomes of pulmonary hypertension in infants with BPD. Objective: To systematically evaluate the risk factors and outcomes associated with pulmonary hypertension in infants with BPD. Methods: We systematically searched the academic literature according to the PRISMA guidelines across five databases (Web of Science, EMBASE, CENTRAL, Scopus, and MEDLINE). We conducted random-effects meta-analyses to evaluate the pulmonary hypertension risk factors in infants with BPD. We also evaluated the overall morbidity- and mortality-related outcomes in infants with BPD and pulmonary hypertension. Results: We found 15 eligible studies representing data from 2156 infants with BPD (mean age, 25.8 ± 0.71 weeks). The overall methodological quality of the included studies was high. Our meta-analysis in infants with severe BPD revealed increased risks of pulmonary hypertension (Odds ratio [OR] 11.2), sepsis (OR, 2.05), preeclampsia (OR, 1.62), and oligohydramnios (OR, 1.38) of being small for gestational age (3.31). Moreover, a comparative analysis found medium-to-large effects of pulmonary hypertension on the total duration of hospital stay (Hedge’s g, 0.50), the total duration of oxygen received (g, 0.93), the cognitive score (g, -1.5), and the overall mortality (g, 0.83) in infants with BPD. Conclusion: We identified several possible risk factors which promoted the onset of pulmonary hypertension in infants with BPD. Moreover, our review sheds light on the morbidity- and mortality-related outcomes associated with pulmonary hypertension in these infants. Our present findings are in line with the existing literature. The findings from this research will be useful in development of efficient risk-based screening system that determine the outcomes associated with pulmonary hypertension in infants with BPD.